Decoding the antineoplastic efficacy of Aplysin targeting Bcl-2: A de novo perspective. (December 2018) - Shakeel, Eram; Sharma, Neha; Akhtar, Salman; Khan, Mohd. Kalim Ahmad; Lohani, Mohtashim; Siddiqui, Mohd. Haris
Graphical abstract: Abstract: The B-cell lymphoma-2 (Bcl-2) family proteins have been attributed to be the key regulators in programmed cell death and apoptosis with a prominent role in human cancer. Understanding the fundamental principles of cell survival and death have been the main cornerstone in cancer drug discovery for identification of novel anticancer agents. In this context the Bcl-2 family of anti-and pro-apoptotic proteins provide an excellent opportunity for development of anticancer agents, as blocking the Bcl-2 or Bcl-XL functionally promotes apoptosis in tumor cells and also sensitize them to chemo- and radiotherapies. The present study reports the identification of novel Aplysin analogs as BCL-2 inhibitors from a sequential virtual screening approach using drug-like, ADMET, docking, pharmacophore filters and molecular dynamics simulation. We identified promising Aplysin analogs that have a potential to be Bcl-2 inhibitors just like the standard drug Obatoclax. One of the compound analog 11 was identified to be a promising inhibitor of Bcl-2 in the docking, pharmacophore and simulation based models.The molecular modeling information provided here can be vital in designing of the novel Bcl-2 inhibitors.